Brain endogenous feedback and degrees of consciousness - Carrara-Augustenborg, Claudia; Pereira Jr., Alfredo [UNESP] (My University, 2012)
We present a model able to account for the mechanisms supporting different degrees of consciousness. We support our proposal with recent evidence from brain morphology and physiology, which indicate that the central nervous system contains two parallel networks (neuronal and astroglial) establishing positive and negative feedback loops. The resonance between the distinct networks can occur in the absence of salient external stimulation and, even when such stimulation occurs, the response of the coupled networks is always dependent on the previous state of their interaction domain. We also explain complex processes occurring below the threshold of awareness as those that deploy the brain's computational resources, although without producing resonant states of sufficient magnitude to determine the individuaĺs overt acknowledgment. Our model, exemplified through the Stadium analogy, affords a plausible account of phenomenal and self-consciousness which, by resting at the outskirts of reportable cognitive activity, traditionally compound the 'hard problem' of consciousness. © 2011 by Nova Science Publishers, Inc. All rights reserved.